Physical Education Curriculum To Enhance Social Skills And Collaboration Among High School Students - Efferirul Indrawan; Reza Hardinata; Tri Bayu Norito; Hendri Munar (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study examines the development of a collaborative-based physical education curriculum designed to enhance students’ social skills and teamwork abilities in senior high schools. The research employed a mixed-methods approach with a quasi-experimental design involving 30 students from a public school in Jambi City. Data were collected through observation sheets, collaboration questionnaires, and teacher reflection notes, then analyzed using t-tests and thematic analysis. The results showed a significant improvement in social skills by 23.5% and collaboration levels by 19.8% after the program implementation. The Sport Education Model (SEM) and Teaching Personal and Social Responsibility (TPSR) approaches effectively fostered teamwork, empathy, and social responsibility. However, challenges remained in teachers’ readiness, facilities, and pedagogical competence. The study concludes that a well-structured collaborative-based physical education curriculum can optimize students’ social development while aligning with 21st-century learning goals and the Kurikulum Merdeka framework.